Antibacterial air purification filter element and preparation method thereof

By using silver chloride nanoparticle/quaternary ammonium polymer composite antibacterial agent in the air purification filter element, the problem of insufficient antibacterial performance of the existing air purification filter element is solved, and efficient air purification and long-lasting antibacterial Effect.

CN119186107AInactive Publication Date: 2024-12-27MEI WEI ER(SHANGHAI) ENVIRONMENAL EQUIP CO LTD

Patent Information

Application Number
CN202411686781.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing air purification filters have shortcomings in antibacterial performance, especially the formaldehyde-removing air purification filters based on oblique pore aluminum honeycomb plates. The antibacterial performance is poor and it is difficult to effectively resist bacteria and virus contamination.

Method used

Using silver chloride nanoparticles/quaternary ammonium polymer composite antibacterial agent, a two-block copolymer of quaternary ammonium compound and a functional monomer containing aromatic nitrogen atoms is prepared through free radical copolymerization, and chlorination is formed in the copolymer. Silver nanoparticles form silver chloride nanoparticles/quaternary ammonium polymer composite antibacterial agent, and combine calcium hydroxide, sodium alginate and bentonite to prepare antibacterial air purification filter element.

Benefits of technology

It has achieved efficient antibacterial effects, with the aldehyde removal rate and benzene removal rate reaching more than 97%, the antibacterial rate reaches more than 98%, and the antibacterial performance is long-lasting, preventing the sterilization rate from reaching more than 96% after 6 months.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an antibacterial air purification filter element and a preparation method thereof, and relates to the technical field of filter materials. The antibacterial air purification filter element is prepared from the following raw materials in parts by weight: 30 to 50 parts of activated carbon, 10 to 15 parts of silver chloride nanoparticle / quaternary ammonium salt polymer composite antibacterial agent, 3 to 5 parts of calcium hydroxide, 8 to 10 parts of simethicone, 3 to 5 parts of sodium alginate and 20 to 30 parts of bentonite. A diblock copolymer of a quaternary ammonium salt compound and an aromatic nitrogen atom-containing functional monomer is prepared through free radical copolymerization, then silver chloride particles are generated in a polymer matrix through in-situ precipitation, and the silver chloride nanoparticle / quaternary ammonium salt polymer composite antibacterial agent is prepared. The antibacterial air purification filter element prepared by the invention has the characteristics of strong antibacterial ability, long antibacterial time, corrosion resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of filter materials, and in particular to an antibacterial air purification filter element and a preparation method thereof. Background Art

[0002] With the acceleration of industrialization and urbanization, pollutants in the air such as PM2.5, PM10, formaldehyde, bacteria and viruses pose a threat to human health; the public's concern for health and quality of life has increased, and the requirements for indoor air quality have increased, which has promoted the development of air purification technology. From the initial simple filtration technology to the current comprehensive application of multiple technologies such as high-efficiency filtration, electrostatic dust removal, photocatalysis, activated carbon adsorption, etc., air purification filter technology has continued to improve. Air filter materials can absorb various harmful particles in the air to prevent them from entering people's living or working environment, reduce the inhalation of harmful substances such as particles into the human lungs, improve people's quality of life, and reduce the occurrence of diseases.

[0003] A Chinese invention patent with publication number CN104689708A discloses a formaldehyde removal air purification filter element based on an oblique hole aluminum honeycomb panel and a preparation method thereof. The air purification filter element comprises a formaldehyde removal coating and an aluminum honeycomb panel, and its formaldehyde coating components include activated carbon, calcium peroxide, calcium oxide, manganese dioxide, potassium carbonate, and an adhesive; the air purification filter element has a good formaldehyde removal rate, but its antibacterial performance is poor. Summary of the invention

[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide an antibacterial air purification filter element and a preparation method thereof.

[0005] To achieve the above object, the present invention is implemented through the following technical solutions: An antibacterial air purification filter element comprises the following raw materials in parts by weight: Activated carbon: 30-50 parts, silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent 10-15 parts, calcium hydroxide: 3-5 parts, dimethyl silicone oil: 8-10 parts, sodium alginate: 3-5 parts, bentonite: 20-30 parts; The silver chloride nanoparticle / quaternary ammonium salt polymer composite antibacterial agent is prepared by the following method: S1: Add chloroacetic acid to a reaction flask, heat it up and melt it, then add 2-methoxy-5-(prop-2-enyl)phenol and concentrated sulfuric acid, then heat it up to 120-140°C, react for 8-10 hours, wash it three times with deionized water after the reaction, dissolve it with dichloromethane, dry it with anhydrous Na2SO4, and then distill it under reduced pressure at 45-55°C for 3-5 hours to obtain a light yellow intermediate, the reaction equation of which is as follows:

[0006] S2: Add the light yellow intermediate and dichloromethane to a reaction flask, slowly drop dodecyl dimethyl tertiary amine, reflux for 5-7h after the dropwise addition is complete, then distill under reduced pressure at 40-50°C for 2-4h, and then recrystallize with an acetone / ethanol mixed solution (acetone / ethanol = 9:1 (V / V)), repeat 3 times, and vacuum dry at 60-70°C for 3-5h to obtain a quaternary ammonium salt compound, the reaction equation of which is shown as follows:

[0007] S3: Under nitrogen protection, add quaternary ammonium salt compound, initiator AIBN, ethyl 2-imidazolyl acrylate and tetrahydrofuran into a reaction bottle, stir, heat to 55-65°C and react for 6-8h. After the reaction is completed, wash with ether 3 times, then extract with acetone for 4-6h, and vacuum dry at 40-50°C for 10-12h to obtain a diblock copolymer. The reaction equation is as follows:

[0008] Among them, m and n are both natural numbers.

[0009] S4: Add DMSO, diblock copolymer and silver p-toluenesulfonate to the reaction bottle in sequence, stir and mix at 0°C, then slowly add CH3NO3, react at room temperature for 2-4h after the addition, add ether, precipitate solid, filter and vacuum dry to obtain silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent.

[0010] The mass ratio of the chloroacetic acid, 2-methoxy-5-(prop-2-enyl)phenol and concentrated sulfuric acid is 12:10:0.1.

[0011] The mass ratio of the light yellow intermediate, dichloromethane and dodecyldimethyl tertiary amine is (10-15):(30-50):(8-12).

[0012] The mass ratio of the quaternary ammonium salt compound, initiator AIBN, 2-imidazolyl ethyl acrylate and tetrahydrofuran is (10-15):(0.8-1.2):(8-20):100.

[0013] The feed mass ratio of the diblock copolymer, silver p-toluenesulfonate, DMSO and CH3NO3 is (8-10):10:(20-30):(10-15).

[0014] The concentration of the concentrated sulfuric acid is 98.3wt%.

[0015] A method for preparing an antibacterial air purification filter element comprises the following steps: S1: Weigh by weight: activated carbon: 30-50 parts, silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent: 10-15 parts, calcium hydroxide: 3-5 parts, dimethyl silicone oil: 8-10 parts, sodium alginate: 3-5 parts, bentonite: 20-30 parts; S2: After mixing all the materials evenly, press them into shape, age them for 4-6 hours, and then send them into a tunnel furnace for sintering in different zones: zone 1: 100-140℃, 150-160min; zone 2: 450-480℃, 50-80min; zone 3: 530-560℃, 40-60min; take them out after cooling, soak them in hot water at 60-70℃ for 1-2 days, take them out and dry them.

[0016] Due to the adoption of the above technical solution, the beneficial effects of the present invention include: (1) A diblock copolymer of a quaternary ammonium salt compound and a functional monomer containing an aromatic nitrogen atom was prepared by free radical copolymerization. Then, silver chloride nanoparticles were generated in the copolymer by an in situ precipitation reaction to prepare a silver chloride nanoparticle / quaternary ammonium salt polymer composite antibacterial agent.

[0017] (2) The silver chloride nanoparticle / quaternary ammonium salt polymer composite antibacterial agent has the advantages of both quaternary ammonium salt organic antibacterial agents and silver-based inorganic antibacterial agents. Due to the coordination effect between the aromatic nitrogen atoms introduced during copolymerization and the silver chloride nanoparticles, the silver chloride nanoparticles can be stabilized, making them less likely to agglomerate and leak, giving full play to the nano-size effect, and having a long-lasting antibacterial effect; at the same time, the long polymer chain stabilizes the silver chloride nanoparticles, and the quaternary ammonium salt compounds in the copolymer matrix synergistically act with the silver chloride nanoparticles to improve their antibacterial activity, which helps to reduce the amount of antibacterial agents used and reduce pollution and damage to the environment. DETAILED DESCRIPTION

[0018] The invention will be further described below in conjunction with the embodiments, but the invention is not limited to these embodiments.

[0019] Example 1 Preparation of silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent: S1: Add 120g of chloroacetic acid to a reaction bottle, heat to 100°C to melt, add 100g of 2-methoxy-5-(prop-2-enyl)phenol and 1g of concentrated sulfuric acid (98.3wt%), then heat to 120°C and react for 10h. After the reaction, wash with deionized water three times (50g of deionized water each time), dissolve with 20ml of dichloromethane, dry with 40g of anhydrous Na2SO4, and then distill under reduced pressure at 45°C for 5h to obtain a light yellow intermediate; S2: 10 g of the light yellow intermediate and 30 g of dichloromethane were added to a reaction flask, and 8 g of dodecyldimethylamine was slowly added dropwise (addition time 10 min). After the addition was completed, the mixture was refluxed for 5 h, and then distilled under reduced pressure at 40 ° C for 4 h. The mixture was recrystallized with an acetone / ethanol mixed solution (acetone / ethanol = 9:1 (V / V)). The mixture was repeated 3 times (100 ml of the mixed solution was used each time), and vacuum dried at 60 ° C for 5 h to obtain a quaternary ammonium salt compound. S3: Under nitrogen protection, 10 g of quaternary ammonium salt compound, 0.8 g of initiator AIBN, 8 g of ethyl 2-imidazole acrylate and 100 g of tetrahydrofuran were added to a reaction bottle, stirred, heated to 55°C for reaction for 8 h, and after the reaction was completed, washed with ether 3 times (50 ml of ether was used each time), then extracted with acetone for 4 h, and vacuum dried at 40°C for 12 h to obtain a diblock copolymer; S4: 20g DMSO, 8g diblock copolymer and 10g silver p-toluenesulfonate were added into the reaction bottle in sequence, stirred and mixed at 0℃, and then 10g CH3NO3 was slowly added dropwise for 2min. After the addition, the mixture was reacted at room temperature for 2h. Then 20ml ether was added to precipitate solid, which was filtered and dried under vacuum at 40℃ for 12h to obtain silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent.

[0020] Example 2 Preparation of silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent: S1: Add 120g of chloroacetic acid to a reaction bottle, heat to 100°C to melt, add 100g of 2-methoxy-5-(prop-2-enyl)phenol and 1g of concentrated sulfuric acid (98.3wt%), then heat to 130°C and react for 9h. After the reaction, wash with deionized water three times (50g of deionized water each time), dissolve with 20ml of dichloromethane, dry with 40g of anhydrous Na2SO4, and then distill at 50°C under reduced pressure for 4h to obtain a light yellow intermediate; S2: Add 12g of light yellow intermediate and 40g of dichloromethane to the reaction bottle, slowly drop 10g of dodecyl dimethyl tertiary amine (drop for 10min), reflux for 6h after the dropwise addition, then distill under reduced pressure at 45℃ for 3h, then recrystallize with acetone / ethanol mixed solution (acetone / ethanol = 9:1 (V / V)), repeat 3 times (each time using 100ml of the mixed solution), vacuum dry at 65℃ for 4h to obtain a quaternary ammonium salt compound. Its H NMR spectrum data are as follows: 1 H NMR (300 MHz, DMSO- d 6) δ 6.94 – 6.80 (m, 3H), 5.93 (ddt, J = 17.1,9.7, 7.5 Hz, 1H), 5.20 (ddt, J= 9.7, 2.2, 1.5 Hz, 1H), 4.99 (ddt, J = 17.0, 2.3,1.5 Hz, 1H), 4.51 (s, 2H), 3.83 (s, 3H), 3.47 (t, J = 8.6 Hz, 2H), 3.34 – 3.25(m, 1H), 3.27 (s, 7H), 1.70 (tt, J = 8.6, 6.2 Hz, 2H), 1.45 – 1.19 (m, 5H), 0.97 – 0.80 (m, 3H), 1.50 – 0.99 (m, 11H), 1.26 (s, 2H). S3: Under nitrogen protection, 12 g of quaternary ammonium salt compound, 1.0 g of initiator AIBN, 14 g of ethyl 2-imidazole acrylate and 100 g of tetrahydrofuran were added to a reaction bottle, stirred, heated to 60°C for reaction for 7 h, and after the reaction was completed, washed with ether 3 times (50 ml of ether was used each time), then extracted with acetone for 5 h, and vacuum dried at 45°C for 11 h to obtain a diblock copolymer; S4: 25g DMSO, 9g diblock copolymer and 10g silver p-toluenesulfonate were added into the reaction bottle in sequence, stirred and mixed at 0℃, and then 12g CH3NO3 was slowly added dropwise for 2min. After the addition, the mixture was reacted at room temperature for 3h. Then 20ml ether was added to precipitate solid, which was filtered and dried under vacuum at 45℃ for 11h to obtain silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent.

[0021] Example 3 Preparation of silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent: S1: Add 120g of chloroacetic acid into a reaction bottle, heat to 100°C to melt, add 100g of 2-methoxy-5-(prop-2-enyl)phenol and 1g of concentrated sulfuric acid (98.3wt%), then heat to 140°C and react for 8h. After the reaction, wash with deionized water three times (50g of deionized water each time), dissolve with 20ml of dichloromethane, dry with 40g of anhydrous Na2SO4, and then distill under reduced pressure at 55°C for 3h to obtain a light yellow intermediate; S2: 15 g of the light yellow intermediate and 50 g of dichloromethane were added to a reaction flask, and 12 g of dodecyldimethylamine was slowly added dropwise (addition time 10 min). After the addition was completed, the mixture was refluxed for 7 h, and then distilled at 50 ° C under reduced pressure for 2 h. The mixture was recrystallized with an acetone / ethanol mixed solution (acetone / ethanol = 9:1 (V / V)). The mixture was repeated 3 times (100 ml of the mixed solution was used each time), and vacuum dried at 70 ° C for 3 h to obtain a quaternary ammonium salt compound. S3: Under nitrogen protection, 15 g of quaternary ammonium salt compound, 1.2 g of initiator AIBN, 20 g of ethyl 2-imidazole acrylate and 100 g of tetrahydrofuran were added to a reaction bottle, stirred, heated to 65 ° C for 6 h, and after the reaction was completed, washed with ether for 3 times (50 ml of ether was used each time), then extracted with acetone for 6 h, and vacuum dried at 50 ° C for 10 h to obtain a diblock copolymer; S4: 30g DMSO, 10g diblock copolymer and 10g silver p-toluenesulfonate were added into the reaction bottle in sequence, stirred and mixed at 0℃, and then 15g CH3NO3 was slowly added dropwise for 2min. After the addition, the mixture was reacted at room temperature for 4h. Then 20ml ether was added to precipitate solid, which was filtered and dried under vacuum at 50℃ for 10h to obtain silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent.

[0022] Example 4 Preparation of air purification filter element: (1) Weigh by weight: activated carbon: 30 g, silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent (prepared in Example 1) 10 g, calcium hydroxide: 3 g, dimethyl silicone oil: 8 g, sodium alginate: 3 g, bentonite: 20 g; (2) After mixing all the materials evenly, press them into shape, age them for 4 hours, and then send them into a tunnel furnace for zone sintering: zone 1: 100°C, 150 min; zone 2: 450°C, 50 min; zone 3: 530°C, 40 min; take them out after cooling, soak them in 60°C hot water for 2 days, take them out and dry them to obtain the air purification filter element.

[0023] Example 5 Preparation of air purification filter element: (1) Weigh by weight: activated carbon: 40 g, silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent (prepared in Example 2) 12 g, calcium hydroxide: 4 g, dimethyl silicone oil: 9 g, sodium alginate: 4 g, bentonite: 25 g; (2) After mixing all the materials evenly, press them into shape, age them for 5 hours, and then send them into a tunnel furnace for zone sintering: zone 1: 120°C, 155 min; zone 2: 460°C, 70 min; zone 3: 545°C, 50 min; take them out after cooling, soak them in 65°C hot water for 1.5 days, take them out and dry them to obtain the air purification filter element.

[0024] Example 6 Preparation of air purification filter element: (1) Weigh by weight: activated carbon: 50 g, silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent (prepared in Example 3) 15 g, calcium hydroxide: 5 g, dimethyl silicone oil: 10 g, sodium alginate: 5 g, bentonite: 30 g; S2: After mixing all the materials evenly, press them into shape, age them for 6 hours, and then send them into a tunnel furnace for zone sintering, zone 1: 140℃, 160min; zone 2: 480℃, 80min; zone 3: 560℃, 60min; take them out after cooling, soak them in 70℃ hot water for 1 day, take them out and dry them to get the air purification filter element.

[0025] Comparative Example 1 The method for preparing an antibacterial air purification filter element is basically the same as that in Example 5, except that the silver chloride nanoparticle / quaternary ammonium salt polymer composite antibacterial agent is not added in step (2).

[0026] Comparative Example 2 The method for preparing an antibacterial air purification filter element is basically the same as that of Example 5, except that the silver chloride nanoparticle / quaternary ammonium salt polymer composite antibacterial agent added in step (2) is replaced by an equal weight of the diblock copolymer prepared in step S3 of Example 2.

[0027] Comparative Example 3 The preparation method of an antibacterial air purification filter element is basically the same as that of Example 5, except that the silver chloride nanoparticle / quaternary ammonium salt polymer composite antibacterial agent added in step (2) is replaced by an equal weight of dodecyl dimethyl tertiary amine.

[0028] Comparative Example 4 A method for preparing an antibacterial air purification filter element is basically the same as that in Example 5, except that the silver chloride nanoparticle / quaternary ammonium salt polymer composite antibacterial agent added in step (2) is replaced by 5.7 g of the diblock copolymer (prepared in Example 2) and 6.3 g of silver p-toluenesulfonate.

[0029] Comparative Example 5 A formaldehyde-removing air purification filter element based on an oblique-hole aluminum honeycomb panel is prepared using the raw materials and methods involved in the specific implementation method No. 2 of the specification with publication number CN104689708A.

[0030] The harmful gas purification performance and antibacterial performance of the air purification filter element prepared in the embodiment and the comparative example were tested, and the test results are shown in Table 1.

[0031] Formaldehyde removal test: Use plastic wrap to seal the transparent box (length: 340mm×width: 250mm×height: 205mm) to form a sealed environment. Use a syringe to take 1.5μL of formaldehyde standard solution each time and inject it into the sealed box. After 2 hours, the diffusion equilibrium is reached; then put the prepared air purification filter into the sealed box to test its formaldehyde removal effect within 6 hours. Record the data every 10 minutes, and take the 6-hour moment as the final formaldehyde removal rate. The benzene removal experiment is the same as above.

[0032] Antibacterial test: The prepared air purification filter element was placed in a sterile culture dish, and then 1 mL of fresh bacterial solution (2×10 5 CFU / mL, Escherichia coli or Staphylococcus aureus), and then place in a 37°C shaker (180 rpm) incubator for 12 hours. After the end, take out, use a micropipette to take 0.2ml of the bacterial solution and apply it to the plate culture medium, then invert the plate in a 37°C constant temperature incubator, and after 24 hours of incubation, take out for observation, count and compare the colony growth.

[0033] Note: All the instruments used in the above microbiological experiments were sterilized by high-pressure steam at 121°C, and all inoculation and coating operations were completed in a clean bench. The bentonite used in the examples and comparative examples of this application is Bentone 38, produced by DKSH Chemical (Shanghai) Co., Ltd.

[0034] Table 1 It can be seen from Table 1 that the air purification filter element prepared in the present application has a formaldehyde removal rate of more than 97%, a benzene removal rate of more than 98%, and an antibacterial rate of more than 98%. The sterilization rate can still reach more than 96% after 6 months, indicating that the air purification filter element prepared in the present application has good formaldehyde removal rate and benzene removal rate, and has high antibacterial and durability.

[0035] Comparative Example 1 is different from Example 5 in that no silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent is added. As can be seen from Table 1, its antibacterial rate is only about 40%, the antibacterial ability is poor, and the antibacterial effect is not long-lasting.

[0036] Comparative Example 2 is different from Example 5 in that the silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent added in step (2) is replaced by an equal weight of the diblock copolymer prepared in step S3. It can be seen from the data in Table 1 that its antibacterial rate is about 60%, and its antibacterial ability is poor.

[0037] Comparative Example 3 is different from Example 5, and the difference is that the silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent added in step (2) is replaced by an equal weight of dodecyl dimethyl tertiary amine. It can be seen from the data in Table 1 that the antibacterial rate is lower than 51%, and the antibacterial effect is poor.

[0038] Comparative Example 4 is different from Example 5 in that the silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent added in step (2) is replaced by an equal weight of diblock copolymer and silver p-toluenesulfonate. It can be seen from the data in Table 1 that the antibacterial rate is about 71%, and the antibacterial effect is average.

[0039] Comparative Example 5 is a formaldehyde removal air purification filter element based on an oblique hole aluminum honeycomb panel prepared using the raw materials and methods in Publication No. CN104689708A. It can be seen from the data in Table 1 that its antibacterial rate is about 45%, and its antibacterial ability and durability are both poor.

[0040] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. However, any equivalent changes, modifications and evolutions made by ordinary technicians in the field without departing from the scope of the technical solution of the present invention by using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. An antibacterial air purification filter element, characterized in that: The invention comprises the following raw materials in parts by weight: Activated carbon: 30-50 parts, silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent 10-15 parts, calcium hydroxide: 3-5 parts, dimethyl silicone oil: 8-10 parts, sodium alginate: 3-5 parts, bentonite: 20-30 parts; The silver chloride nanoparticle / quaternary ammonium salt polymer composite antibacterial agent is prepared by the following method: S1: Add chloroacetic acid to a reaction flask, heat it up to melt, then add 2-methoxy-5-(prop-2-enyl)phenol and concentrated sulfuric acid, then heat it up to 120-140°C and react for 8-10 hours to obtain a light yellow intermediate; S2: Add the light yellow intermediate and dichloromethane into a reaction flask, slowly drop dodecyldimethylamine, and reflux for 5-7h after the dropwise addition to obtain a quaternary ammonium salt compound; S3: under nitrogen protection, add quaternary ammonium salt compound, initiator AIBN, ethyl 2-imidazolylacrylate and tetrahydrofuran into a reaction bottle, stir, raise the temperature to 55-65° C. and react for 6-8 hours to obtain a diblock copolymer; S4: Add DMSO, diblock copolymer and silver p-toluenesulfonate to the reaction bottle in sequence, stir and mix at 0°C, then slowly add CH3NO3, react at room temperature for 2-4h after the addition, add ether, precipitate solid, filter and vacuum dry to obtain silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent.

2. The antibacterial air purification filter element according to claim 1, characterized in that: In step S1, the mass ratio of chloroacetic acid, 2-methoxy-5-(prop-2-enyl)phenol and concentrated sulfuric acid is 12:10:0.

1.

3. The antibacterial air purification filter element according to claim 1, characterized in that: In step S2, the mass ratio of the light yellow intermediate, dichloromethane and dodecyldimethyl tertiary amine is (10-15):(30-50):(8-12).

4. The antibacterial air purification filter element according to claim 1, characterized in that: In step S3, the mass ratio of the quaternary ammonium salt compound, initiator AIBN, 2-imidazolyl ethyl acrylate and tetrahydrofuran is (10-15):(0.8-1.2):(8-20):

100.

5. The antibacterial air purification filter element according to claim 1, characterized in that: In step S4, the mass ratio of the diblock copolymer, silver p-toluenesulfonate, DMSO and CH3NO3 is (8-10):10:(20-30):(10-15).

6. The antibacterial air purification filter element according to claim 1, characterized in that: In step S1, the concentration of concentrated sulfuric acid is 98.3wt%.

7. A method for preparing the antibacterial air purification filter element according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Weigh by weight: 30-50 parts of activated carbon, 10-15 parts of silver chloride nanoparticles / quaternary ammonium salt polymer composite antibacterial agent, 3-5 parts of calcium hydroxide, 8-10 parts of dimethyl silicone oil, 3-5 parts of sodium alginate, and 20-30 parts of bentonite; (2) After the materials are mixed evenly, they are pressed into shape, aged for 4-6 hours, and then sent to a tunnel furnace for zone sintering, zone 1: 100-140°C, 150-160min; Zone 2: 450-480℃, 50-80min; Zone 3: 530-560℃, 40-60min; After cooling, take it out, soak it in 60-70℃ hot water for 1-2 days, take it out and dry it.

Citation Information

Patent Citations

  • Composite antimicrobial of nanometer silver bromide polymer and preparation method thereof

    CN102690481A

  • Air cleaning filter core and preparation method thereof

    CN103381321A

  • Preparation method of quaternary ammonium salt polymer antibacterial agent and silver-loaded compound antibacterial agent thereof on basis of ATRP method

    CN105801734A

  • Preparation method of quaternary ammonium salt type oligomeric surfactant

    CN118666699A

Cited By

  • Super-hydrophobic mildew-proof anti-algae polymer preparation and preparation process thereof

    CN122168163A

  • Super-hydrophobic mildew and algae resistant polymer preparation and its preparation process

    CN122168163B